2011
DOI: 10.1371/journal.pone.0018955
|View full text |Cite
|
Sign up to set email alerts
|

Classical Mus musculus Igκ Enhancers Support Transcription but not High Level Somatic Hypermutation from a V-Lambda Promoter in Chicken DT40 Cells

Abstract: Somatic hypermutation (SHM) of immunoglobulin genes is initiated by activation-induced cytidine deaminase (AID) in activated B cells. This process is strictly dependent on transcription. Hence, cis-acting transcriptional control elements have been proposed to target SHM to immunoglobulin loci. The Mus musculus Igκ locus is regulated by the intronic enhancer (iE/MAR) and the 3′ enhancer (3′E), and multiple studies using transgenic and knock-out approaches in mice and cell lines have reported somewhat contradict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…The three Igκ enhancers, intron ( IgκEi ), 3′ ( IgκE3′ ), and Ed ( IgκEd ) [47], of mice and humans (Figures 5A and S5) induced low or modest levels of GFP loss when assayed on their own (Figure 5B), consistent with previous analyses [36],[38]. However, when two Igκ enhancers were combined ( IgκEi + IgκE3′ or IgκE3′ + IgκEd ), GFP loss markedly increased, and when the three human Igκ enhancers were combined, GFP loss reached 50.9% (Figure 5B).…”
Section: Resultssupporting
confidence: 87%
“…The three Igκ enhancers, intron ( IgκEi ), 3′ ( IgκE3′ ), and Ed ( IgκEd ) [47], of mice and humans (Figures 5A and S5) induced low or modest levels of GFP loss when assayed on their own (Figure 5B), consistent with previous analyses [36],[38]. However, when two Igκ enhancers were combined ( IgκEi + IgκE3′ or IgκE3′ + IgκEd ), GFP loss markedly increased, and when the three human Igκ enhancers were combined, GFP loss reached 50.9% (Figure 5B).…”
Section: Resultssupporting
confidence: 87%
“…These studies imply that transcription driven by any promoter might support SHM. This notion is consistent with later studies suggesting that the level of transcription is not necessarily correlated with the level of mutations [80, 81]. It has been long proposed that the mutator enzyme (now known as AID) may associate with RNAP II to mediate SHM [82].…”
Section: Cis Regulatory Elements In Shm Targetingsupporting
confidence: 88%
“…4), strongly argues against the notion that E boxes are sufficient for SHM targeting. The distinct conclusions arising from the two studies are likely due to the weak signal provided by the GFP reversion assay used by Tanaka et al (34) and their use of murine enhancers that we (9) and others (39) have shown have poor SHM targeting activity in DT40 cells. In contrast, our analysis rests on a robust SHM assay and DIVAC sequences that contain much or most of the known DIVAC function of the chicken IgL locus (26).…”
Section: Discussionmentioning
confidence: 83%